A rare urinary JC virus reactivation after long-term therapy with rituximab. (February 2021) - Di Maida, Fabrizio; Viola, Lorenzo; Lambertini, Luca; Mari, Andrea; Mencarini, Jessica; Borchi, Beatrice; Carini, Marco; Zammarchi, Lorenzo; Minervini, Andrea
Highlights: JC virus is able to elicit its pathological effect at the level of the urinary tract. Long-term therapy with rituximab represents a possible trigger for JC virus reactivation. JC virus-associated nephropathy and uropathy must be considered in the differential diagnosis of patients treated previously with biological therapies and/or who are potentially immunocompromised (subjects with a congenital or acquired immune deficiency, kidney transplantation recipients), especially when complaining of urinary tract infection symptoms. Abstract: The possible role of JC virus in determining urinary tract involvement has only recently been recognized. The case of a man with laboratory-confirmed JC virus replication in the urine after a maintenance schedule of rituximab administered for a lymphoproliferative disorder is reported herein. The patient developed severe renal and urinary tract impairment, characterized by the onset of nephropathy, bilateral ureteral strictures, and a serious reduction in vesical compliance, ultimately requiring an ileal neobladder configuration. The renal and urinary tract involvement was finally attributed to JC virus reactivation. This observation suggests that renal and urinary tract diseases related to JC virus might be associated with long-term rituximab treatment.